Odpowiedź:
[tex]\begin{cases}-8x-6y=-26\ \ /:2\\-x+4y=16\end{cases}\\\\\\\begin{cases}-4x-3y=-13\\-x+4y=16\ \ /*(-4)\end{cases}\\\\\\+\begin{cases}-4x-3y=-13\\4x-16y=-64\end{cases}\\----------\\-19y=-77\ \ /:(-19)\\\\y=\frac{77}{19}\\\\\\-x+4*\frac{77}{19}=16\\\\-x+\frac{308}{19}=16\\\\-x=16-\frac{308}{19}\\\\-x=16-16\frac{4}{19}\\\\-x=-\frac{4}{19}\ \ /*(-1)\\\\x=\frac{4}{19}\\\\\begin{cases}x=\frac{4}{19}\\y=\frac{77}{19}\end{cases}[/tex]
[tex]\frac{x+1}{2}-2(x+1)=-5-\frac{x+1}{4}\\\\\frac{x+1}{2}-2x-2=-5-\frac{x+1}{4}\ \ /*4\\\\2(x+1)-8x-8=-20-(x+1)\\\\2x+2-8x-8=-20-x-1\\\\-6x-6=-21-x\\\\-6x+x=-21+6\\\\-5x=-15\ \ /:(-5)\\\\x=3[/tex]